Metabarcoding of ichthyoplankton communities associated with a highly dynamic shelf region of the southwest Indian Ocean - Ashrenee Govender; Sean T. Fennessy; Sean N. Porter; Johan C. Groeneveld (PLoS ONE, 2023)
Drifting fish eggs and larvae (ichthyoplankton) can be identified to species using DNA metabarcoding, thus allowing for post hoc community analyses at a high taxonomic resolution. We undertook a regional-scale study of ichthyoplankton distribution along the east coast of South Africa, focused on the contrasting environments of the tropical Delagoa and subtropical Natal Ecoregions, and on exposed and sheltered shelf areas. Zooplankton samples were collected with tow nets at discrete stations along cross-shelf transects (20–200 m depth) spaced along a latitudinal gradient that incorporates a known biogeographical boundary. Metabarcoding detected 67 fish species, of which 64 matched prior distribution records of fishes from South Africa, with the remaining three known from the Western Indian Ocean. Coastal, neritic and oceanic species were present, from epi- and mesopelagic to benthopelagic and benthic adult habitats. By family, Myctophidae (10 species), Carangidae, Clupeidae, Labridae (each with 4 species) and Haemulidae (3 species) were most speciose. Ichthyoplankton community composition varied significantly with latitude, distance to coast, and distance to the shelf edge. Small pelagic fishes had the highest frequency of occurrence: Engraulis capensis, Emmelichthys nitidus and Benthosema pterotum increased in frequency towards the north, whereas Etrumeus whiteheadi increased towards the south. Chub mackerel Scomber japonicus accounted for most variability related to distance from the coast, whilst African scad Trachurus delagoa correlated with distance to the shelf edge. Dissimilarity between communities in the Delagoa and Natal Ecoregions was 98–100%, whereas neighbouring transects located within the sheltered KwaZulu-Natal Bight had lower dissimilarity (56–86%). Onshore transport of ichthyoplankton by Agulhas Current intrusions plausibly explained the abundance of mesopelagic species over the shelf. Metabarcoding followed by community analysis revealed a latitudinal gradient in the ichthyoplankton, associations with coastal and shelf-edge processes, and evidence of a spawning area in the sheltered KwaZulu-Natal Bight.